Prognostic implications of N-terminal pro-B-type natriuretic peptide in patients with normal left ventricular ejection fraction undergoing transcatheter aortic valve implantation. (15th February 2020) - Seoudy, Hatim; Kuhn, Christian; Frank, Johanne; Eden, Matthias; Rangrez, Ashraf Yusuf; Lutter, Georg; Frey, Norbert; Frank, Derk
Abstract: Background: Biomarkers may significantly improve risk stratification algorithms for patients undergoing transcatheter aortic valve implantation (TAVI). While N-terminal pro-B-type natriuretic peptide (NT-proBNP) is established as a biomarker in the context of heart failure, its prognostic implications in patients with normal left ventricular ejection fraction (LVEF) undergoing TAVI are unclear. Methods: A total of 504 TAVI patients with normal LVEF were analyzed. Based on preprocedural NT-proBNP levels, patients were stratified into two groups comparing the upper quartile ("Q4", n = 126) with the lower three quartiles ("Q1–3", n = 378). The primary outcome of our study was survival. Results: The "Q4" group included more men (46.8% vs. 34.9%, p = 0.017), had higher rates of atrial fibrillation (55.6% vs. 28.3%, p < 0.001) and showed features of more advanced aortic stenosis (mean pressure gradient 49 mmHg vs. 40 mmHg, aortic valve area 0.6 cm 2 vs. 0.7 cm 2 ; p < 0.001, respectively). The "Q4" group was also characterized by more extensive cardiac remodeling including severe diastolic dysfunction (18.1% vs. 6.5%, p < 0.001) and left atrial dilation (26.8% vs. 10.8%, p < 0.001). Kaplan-Meier analysis demonstrated superior survival of the "Q1–3" group (median follow-up 22.1 months, log-rank test p < 0.001). In a multivariable analysis, preprocedural NT-proBNP emerged as a significant risk factor for all-cause mortality after TAVI (HR 1.87, CI 1.31–2.65, p < 0.001). Conclusions: NT-proBNP is associated with survival in TAVI patients with normal LVEF. In this patient group, preprocedural NT-proBNP levels do not only correlate with aortic stenosis, but reflect advanced cardiovascular dysfunction, including HFpEF, that might not be completely reversible after TAVI. Highlights: In TAVI patients with normal LVEF, preprocedural NT-proBNP levels are associated with postprocedural survival. NT-proBNP does not only reflect aortic stenosis severity, but also more complex cardiac dysfunction, including HFpEF. NT-proBNP might be valuable as part of preprocedural risk assessment strategies in TAVI patients with normal LVEF. NT-proBNP might also aid in identifying high-risk patients who are less responsive to TAVI.